Defense mechanisms of Salmonella against antibiotics: a review - Punchihewage-Don, Anuradha Jeewantha; Ranaweera, Priyanka Nilmini; Parveen, Salina (Frontiers in Antibiotics, 2024)
Salmonella is a foodborne pathogenic bacterium that causes salmonellosis worldwide. Also, Salmonella is considered a serious problem for food safety and public health. Several antimicrobial classes including aminoglycosides, tetracyclines, phenols, and β-Lactams are used to treat Salmonella infections. Antibiotics have been prescribed for decades to treat infections caused by bacteria in human and animal healthcare. However, intensive use of antibiotics resulted in antibiotic resistance (AR) among several foodborne bacteria including Salmonella. Furthermore, Multi-Drug Resistance (MDR) of Salmonella has increased dramatically. In addition to MDR Salmonella, Extensively Drug Resistant (XDR) as well as Pan Drug Resistant (PDR) Salmonella were reported globally. Therefore, increasing AR is becoming a serious universal public health crisis. Salmonella developed many mechanisms to ensure its survival against antimicrobials. The most prominent defense mechanisms against these antibiotics include enzymatic inactivation, expelling drugs from the cell through efflux pumps, altering the structure of drugs, and changing or protecting the targets of drugs. Additionally, the formation of biofilms and plasmid-mediated antibiotic resistance by Salmonella, enhancing its resistance to various antibiotics, making it a challenging pathogen in both healthcare and food industry settings. This review focuses exclusively on providing a detailed overview of the mechanisms of AR in Salmonella.